2014
DOI: 10.1097/prs.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Pulmonary Complications and Hospital Length of Stay with a Clinical Care Pathway after Head and Neck Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…By identifying aspiration/pneumonia as postoperative complications predisposing patients to readmission, targeted perioperative interventions may be designed to mitigate its risk. For example, prior studies have demonstrated how certain interventions (including incentive spirometry, chest physiotherapy, and oral care) can reduce postoperative pulmonary complications . In addition, a recent study demonstrated how the implementation of a standardized speech and language pathology‐driven postoperative swallowing assessment and intervention care pathway essentially eliminated 30‐day dysphagia‐related readmissions in TORS patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By identifying aspiration/pneumonia as postoperative complications predisposing patients to readmission, targeted perioperative interventions may be designed to mitigate its risk. For example, prior studies have demonstrated how certain interventions (including incentive spirometry, chest physiotherapy, and oral care) can reduce postoperative pulmonary complications . In addition, a recent study demonstrated how the implementation of a standardized speech and language pathology‐driven postoperative swallowing assessment and intervention care pathway essentially eliminated 30‐day dysphagia‐related readmissions in TORS patients …”
Section: Discussionmentioning
confidence: 99%
“…For example, prior studies have demonstrated how certain interventions (including incentive spirometry, chest physiotherapy, and oral care) can reduce postoperative pulmonary complications. 42,43 In addition, a recent study demonstrated how the implementation of a standardized speech and language pathology-driven postoperative swallowing assessment and intervention care pathway essentially eliminated 30-day dysphagia-related readmissions in TORS patients. 20 There are limitations to this study and the results should only be interpreted in the context of its study design.…”
Section: Discussionmentioning
confidence: 99%
“…Care pathways may have a beneficial postdischarge impact for a number of reasons. First, patients treated on a care pathway tend to have shorter hospitalizations and fewer complications . This could then result in a less complicated postdischarge course and, therefore, less postdischarge resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway patients who deviated from the pathway were included in all analyses. The details of the inpatient care pathway have been previously published …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation